2016
DOI: 10.1128/jvi.00591-16
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Myticin C Peptide from Mussel: an Ancient Defense against Herpesviruses

Abstract: Little is known about the antiviral response in mollusks. As in other invertebrates, the interferon signaling pathways have not been identified, and in fact, there is a debate about whether invertebrates possess antiviral immunity similar to that of vertebrates. In marine bivalves, due to their filtering activity, interaction with putative pathogens, including viruses, is very high, suggesting that they should have mechanisms to address these infections. In this study, we confirmed that constitutively expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 49 publications
1
57
0
Order By: Relevance
“…Still, knowledge about the antiviral response in bivalves, as in all invertebrates, is scarce. The discussion about whether invertebrates possess antiviral immunity is ongoing and further enhanced by recent works, such as the study presented by Novoa et al (2016). In this study, they confirmed that constitutively expressed myticins in naïve mussels made oyster hemocytes resistant to ostreid herpesvirus 1 (OsHV-1).…”
Section: Introductionsupporting
confidence: 73%
“…Still, knowledge about the antiviral response in bivalves, as in all invertebrates, is scarce. The discussion about whether invertebrates possess antiviral immunity is ongoing and further enhanced by recent works, such as the study presented by Novoa et al (2016). In this study, they confirmed that constitutively expressed myticins in naïve mussels made oyster hemocytes resistant to ostreid herpesvirus 1 (OsHV-1).…”
Section: Introductionsupporting
confidence: 73%
“…Myticin C is an antimicrobial peptide widely studied in mussels. Some of its functions are directly related to the killing of pathogens: its antibacterial [8] and antiviral properties [10,21] have been reported. In line with these properties, one of the most expressed genes in the transcriptome analysis is the tripartite motif-containing protein 56 (TRIM56).…”
Section: Discussionmentioning
confidence: 99%
“…Hemocytes are capable of encapsulating and phagocyting foreign particles or pathogens, as well as synthesizing and releasing cytotoxic factors [8], including AMPs that represent key components of the mussel immune system. These small cationic peptides are cysteine-rich molecules, and are traditionally involved in the response to bacteria, some fungi, and viruses [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mussels, the hemocytes are also involved in the host immune system as half of the genes expressed by these cells are antimicrobial peptides such as myticins, mytilins and myticilins 17 . Myticin C for example inhibits the replication of bacteria 18 , fish viruses 19 , and human herpesvirus 20 . In adult oysters, the gill was reported to be the potential hematopoietic site 21,22 .…”
mentioning
confidence: 99%